Alterations in dynamics of counterjet injection technique in presence of real gas effects. (2022) - Patil, Ajay; Kulkarni, Vinayak
Abstract: Large wave drag is common problem encountered for flights driving at high speeds. It should be dealt with utmost care for better design of long range flights cruising at high speeds. Studies found in the literature only deals with computations or experiment that are carried at lower stagnation temperature or considering perfect gas flow. Thus, the present work incorporates the real gas effects on various flow features like Mach disk diameter, Mach disk location and recirculation pressure. Further the effect of various freestream Mach number (M∞ ) and freestream total enthalpy (Ho ) are observed on wall pressure for blunt body hemisphere considering real gas reactions by means of in house perfect and real gas solvers at hypersonic speeds. Pressure ratio of opposing jet is fixed as 15 while temperature ratio is fixed as 1. Results reveals that the pressure on the object lowers with the increase in M∞ especially upstream of maximum surface pressure point both for the reacting as well as the perfect solver. Surface pressure is found to be much higher at elevated freestream total enthalpy in comparison of smaller freestream total enthalpy for reacting solver while surface pressure almost shows similar trend at all Freestream total enthalpy for perfect solver case. Surface pressure for perfect solver is found to be lower than surface pressure for reacting solver for all the cases studied and this reduction is significant at higher M∞ . Drag on body is rising with Freestream total enthalpy but this rate of drag enhancement diminishes at higher M∞ .